(untitled) (Annals of Medical Research, 2022)
Aim: We aimed to determine the effects of acrylamide (AA) and crocin (Cr) on rat lung tissues. Materials and Methods: Forty Wistar albino rats were divided into control, AA, Cr, and AA + Cr groups. Rats were administered 25 mg/kg AA and 50 mg/kg Cr for 21 days. After 21 days, malondialdehyde (MDA), reduced glutathione (GSH), total antioxidant status (TAS), total oxidant status (TOS), oxidative stress index (OSI), superoxide dismutase (SOD), catalase (CAT) and protein levels were measured in rat lung tissues. Results: The analysis of the rat lung tissues revealed that oxidant parameter markers (MDA, TOS, OSI) increased and antioxidant parameter markers (GSH, TAS, SOD, CAT) decreased in the AA group when compared to all other groups (p <0.05). A significant increase was determined in antioxidant capacity (GSH, TAS, SOD, CAT) in the Cr-treatment group when compared to all other groups (p <0.05). We found a significant improvement in oxidant-antioxidant parameters in the AA + Cr group when compared to the AA group (p <0.05). Conclusion: This study was the first of its kind in the literature and revealed that AA administration led to damages in lung tissue. It could be suggested that this was due to an increase in oxidant levels and oxidative stress. Cr exerted a powerful antioxidant effect in lung tissues. Against AA toxicity, we recommend the consumption of Cr to improve antioxidant capacity.